5x - 2y = 05x - 5x - 2y = 0 - 5x-2y = - 5x(-2y)/-2 = (-5x)/-2y = (5/2)x where the slope is 5/2 and the y-intercept is 0.
(5x - 2y)(5x + 2y)
if you mean 5x -2y = 10 then y = 2.5x -5
5x-2y=11 -2y=-5x+11 y=(5/2)x - 11/2 Slope is 5/2
If you mean: 2y+5x = 13 and 2y-3x = 5 then it works out that x = 1 and y = 4
5y explanaition 5x-5x=0, 0-2y=-2y, -2y+7y=5y
5x - 2y = 05x - 5x - 2y = 0 - 5x-2y = - 5x(-2y)/-2 = (-5x)/-2y = (5/2)x where the slope is 5/2 and the y-intercept is 0.
To do this equation, there would have to be an = in it. If you mean 5x-2y=4, then: 5x-2y=4 -5x -5x = -2y=4-5x Hope this helped!
5x + (3y-x) + (10-2y) = 5x + 3y - x + 10 -2y = 5x - x + 3y - 2y + 10 = 4x + y +10
(5x - 2y)(5x + 2y)
-5x-2y=10
if you mean 5x -2y = 10 then y = 2.5x -5
5x-2y=11 -2y=-5x+11 y=(5/2)x - 11/2 Slope is 5/2
5x-2y=-3 -2y=-5x-3 y=(5/2)x+3/2 slope is 5/2
5x - 2y = 10 2y = 5x - 10 y = 2.5x - 5......which is the equation in slope intercept form.
5x+2y>8, y≤4 5x+2(4)>8 5x+8>8 5x>0 x>0
5x - 2y - 70 is not an equation and therefore cannot be converted. However, the equation 5x - 2y = 70 converts to slope intercept form the following way: 5x - 2y = 70 = -2y = -5x + 70 = -2y/-2 = -5x/-2 + 70/-2 = y = 5/2 x + (-35) = y = 5/2 x - 35 slope: 5/2 y-intercept: -35 ---- the above answer is wrong due wikianswer's punctuation limit. Which does not allow the "=" The problem is 5x-2y=70 here's how to rewrite the equation. 5x-2y=70 subtract 5x from both side. 2y=70-5x divide both side by 2 y=70-5x/2